Whole-body vibration of mice induces articular cartilage degeneration with minimal changes in subchondral bone. Issue 5 (May 2017) - McCann, M.R.; Yeung, C.; Pest, M.A.; Ratneswaran, A.; Pollmann, S.I.; Holdsworth, D.W.; Beier, F.; Dixon, S.J.; Séguin, C.A.
Summary: Objective: Low-amplitude, high-frequency whole-body vibration (WBV) has been adopted for the treatment of musculoskeletal diseases including osteoarthritis (OA); however, there is limited knowledge of the direct effects of vibration on joint tissues. Our recent studies revealed striking damage to the knee joint following exposure of mice to WBV. The current study examined the effects of WBV on specific compartments of the murine tibiofemoral joint over 8 weeks, including microarchitecture of the tibia, to understand the mechanisms associated with WBV-induced joint damage. Design: Ten-week-old male CD-1 mice were exposed to WBV (45 Hz, 0.3  g peak acceleration; 30 min/day, 5 days/week) for 4 weeks, 8 weeks, or 4 weeks WBV followed by 4 weeks recovery. The knee joint was evaluated histologically for tissue damage. Architecture of the subchondral bone plate, subchondral trabecular bone, primary and secondary spongiosa of the tibia was assessed using micro-CT. Results: Meniscal tears and focal articular cartilage damage were induced by WBV; the extent of damage increased between 4 and 8-week exposures to WBV. WBV did not alter the subchondral bone plate, or trabecular bone of the tibial spongiosa; however, a transient increase was detected in the subchondral trabecular bone volume and density. Conclusions: The lack of WBV-induced changes in the underlying subchondral bone suggests that damage to the articular cartilage may be secondary to the meniscal injury we detected. Our findings underscore the need for further studies to assess the safety of WBV in the human population to avoid long-term joint damage.